2009
DOI: 10.1523/jneurosci.0559-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Natural Scene Categories Revealed in Distributed Patterns of Activity in the Human Brain

Abstract: Human subjects are extremely efficient at categorizing natural scenes, despite the fact that different classes of natural scenes often share similar image statistics. Thus far, however, it is unknown where and how complex natural scene categories are encoded and discriminated in the brain. We used functional magnetic resonance imaging (fMRI) and distributed pattern analysis to ask what regions of the brain can differentiate natural scene categories (such as forests vs mountains vs beaches). Using completely di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

43
300
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(347 citation statements)
references
References 54 publications
43
300
2
2
Order By: Relevance
“…In 2011, Kravitz et al [23] applied MDS to reconstruct and visualize representational dissimilarity structure derived from the distributed neural responses to 96 diverse real-world scenes. The authors found, contrary to previous studies [29,30], that representations in the ventral temporal parahippocampal place area (PPA) were characterized primarily by the spatial factor of expanse (open, closed) and in early visual cortex (EVC) primarily by distance (near, far), not by category or context. Kriegeskorte et al [22] applied hierarchical clustering analysis of response patterns in human brain evoked by 92 ungrouped-object stimuli photos, and found that object representation was inherently categorical in inferotemporal cortex (IT): animate and inanimate objects form the two major clusters; faces and bodies form subclusters within the animate cluster.…”
Section: Representing Dissimilarity Structure Of Response Patterns Tocontrasting
confidence: 90%
“…In 2011, Kravitz et al [23] applied MDS to reconstruct and visualize representational dissimilarity structure derived from the distributed neural responses to 96 diverse real-world scenes. The authors found, contrary to previous studies [29,30], that representations in the ventral temporal parahippocampal place area (PPA) were characterized primarily by the spatial factor of expanse (open, closed) and in early visual cortex (EVC) primarily by distance (near, far), not by category or context. Kriegeskorte et al [22] applied hierarchical clustering analysis of response patterns in human brain evoked by 92 ungrouped-object stimuli photos, and found that object representation was inherently categorical in inferotemporal cortex (IT): animate and inanimate objects form the two major clusters; faces and bodies form subclusters within the animate cluster.…”
Section: Representing Dissimilarity Structure Of Response Patterns Tocontrasting
confidence: 90%
“…Forty-eight different perceptual masks were created. Each was a colored picture of a mixture of white noise at different spatial frequencies on which a naturalistic texture was superimposed (31). Within a scanning session each of the presented pictures was unique.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously found that information about scene category is contained in patterns of fMRI activity in the parahippocampal place area (PPA), the retrosplenial cortex (RSC), the lateral occipital complex (LOC), and the primary visual cortex (V1) (12). PPA activity patterns appear to be linked most closely to human behavior (12), and activity in V1, PPA, and RSC elicited by good exemplars of scene categories contains significantly more scene category-specific information than patterns elicited by bad exemplars do (13).…”
mentioning
confidence: 99%
“…PPA activity patterns appear to be linked most closely to human behavior (12), and activity in V1, PPA, and RSC elicited by good exemplars of scene categories contains significantly more scene category-specific information than patterns elicited by bad exemplars do (13). Interestingly, inspection of the average images of good and bad exemplars of a category suggests that good exemplars may contain more defined global structure apparent in the images than bad exemplars (13), suggesting that features that capture global information in the image may play a particularly important role in scene categorization.…”
mentioning
confidence: 99%
See 1 more Smart Citation